Religion and the Catholic Church's View on (Heart) Transplantation: A Recent Statement of Pope Benedict XVI and its Practical Impact - Schwarz, Ernst Rüdiger (Journal of religion and health, 2011)
Heart transplantation is performed on approximately 4,000 patients per year worldwide and is considered the last resort for treatment of end-stage heart diseases. Due to persistent organ shortage, resources are limited, waiting periods are extensive, and patients still die while being on a waiting list for transplantation. The role of all churches and the support of the representatives of the churches are critical for the spiritual wellbeing of patients awaiting heart transplantation as well as for prospective individual organ donors and their families. The supportive role of the Roman Catholic Church and the recent statement of Pope Benedict XVI on organ donation are discussed.